O professor iniciante do curso de Licenciatura em Biologia e a formação dos professores da escola básica - Lopes, Sueli Terezinha Fernandes (2019)
Many challenges influence the development process of university professors, especially those working with teaching licensure, shaping primary school teachers. Very few papers analyze the challenges that these professors face early on in their careers. This work tries to understand how biology university professors begin their careers and the main factors behind their professional placement. Who are the entry level professors in biology licensure and how are they shaping future teachers? What challenges do they face and what are their expectations? Authors such as Imbernón, Tardif, Schulman, Feixas, Altet; Perrenoud e Paquay, André, Almeida, Vaillant, Mizukami, among others provided the theoretical framework for this thesis. The research process used qualitative data sourced form documents and interviews with five entry level biology professors, one from a public university, three from private universities and one from a non-profit institution. Among which only one had previous experience teaching at the high school level. The professors showed commitment to new methods in their classes according to prose analysis of the data. The main challenges identified by professors were focused on work conditions in a few institutions and their lack of pedagogical training, the later was also confirmed in the analysis of biology courses’ syllabus. The lack of support in the beginning of their careers was highlighted and the need for greater support was identified by all professors. They also mentioned that exchanging experiences with colleagues would have been an important source of support. This research showed that previous experience in primary education allowed for greater comfort in the new career which shows that the knowledge from previous experiences is helpful for university professors in the beginning of their careers